2011
DOI: 10.1242/jeb.053470
|View full text |Cite
|
Sign up to set email alerts
|

Static electric fields modify the locomotory behaviour of cockroaches

Abstract: SUMMARYStatic electric fields are found throughout the environment and there is growing interest in how electric fields influence insect behaviour. Here we have analysed the locomotory behaviour of cockroaches (Periplaneta americana) in response to static electric fields at levels equal to and above those found in the natural environment. Walking behaviour (including velocity, distance moved, turn angle and time spent walking) were analysed as cockroaches approached an electric field boundary in an open arena,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Electric fields can act on mechanoreceptors of their cuticular appendages if these appendages are charged, and indeed such fields have been used to stimulate insect mechanosensory organs [15,27]. Electric fields induce responses in insects [7,8,28]. A biologically relevant property of body surface charge in pollinating insects was traced to the opposite polarity of their body surface charge to that of flowers, potentially facilitating pollen collection and possibly leaving a cue after electrical neutralization of the flowers' electric field [9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Electric fields can act on mechanoreceptors of their cuticular appendages if these appendages are charged, and indeed such fields have been used to stimulate insect mechanosensory organs [15,27]. Electric fields induce responses in insects [7,8,28]. A biologically relevant property of body surface charge in pollinating insects was traced to the opposite polarity of their body surface charge to that of flowers, potentially facilitating pollen collection and possibly leaving a cue after electrical neutralization of the flowers' electric field [9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila, like cockroaches [6] and other Diptera [31], show clear avoidance of static electric fields [32]. What is notable about Drosophila is that the wings had a major role to play in avoidance, while the antennae are involved in cockroaches [7].…”
Section: (B) Avoidance Movementsmentioning
confidence: 99%
“…Other studies have suggested that accumulation of charge during flight could assist foraging and pollination through the transfer of pollen grains onto plant stigmata [3][4][5]. Static electric fields can also lead to changes in walking [6,7] and avoidance behaviour [6,8], and influence locomotion and agitation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Other insects have been shown to detect and behaviourally respond to electric fields with aversive reactions. For example, a proprioreceptor at the antennal base of American cockroaches, Periplaneta americana (L.) (Blattodea: Blattidae), detects electric fields prompting an avoidance response (Hunt et al, 2005;Newland et al, 2008;Jackson et al, 2011). The cabbage looper, Trichoplusia ni (H€ ubner), avoids static electric fields (Perumpral et al, 1978).…”
Section: Introductionmentioning
confidence: 99%